Measuring the implementation of ecodesign management practices: A review and consolidation of process-oriented performance indicators. (10th July 2017) - Rodrigues, Vinícius P.; Pigosso, Daniela C.A.; McAloone, Tim C.
Abstract: Ecodesign plays an important role in manufacturing companies' quest for improved sustainability performance. However, many ecodesign efforts are geared towards tackling single-issue discrete improvements, in contrast to operationalizing, measuring and acting upon the consistent improvement of ecodesign implementation and management. To enable a systematic and streamlined integration of ecodesign practices into the product development processes, adequate mechanisms are needed to capture and measure performance improvements, and thereby achieve consistent improvements in a company's efforts towards enhanced sustainability performance. In face of this challenge, this paper aims at providing organizations with a set of process-oriented indicators to supporting and enhancing ecodesign implementation and management. This research was grounded on a 2-phase approach to (i) cross-analyze performance indicators from literature against ecodesign practices at the process level and (ii) propose, evaluate and consolidate new indicators. After being subjected to the evaluation of 8 experts in ecodesign, a repository is presented with 27 indicators from literature and a set of 114 newly proposed indicators for companies to customize, adapt, mix and derive according to their needs, strategic drivers and overall context.